Academic-Community Hospital Comparison of Vulnerabilities in Door-to-Needle Process for Acute Ischemic Stroke. (October 2015) - Prabhakaran, Shyam; Khorzad, Rebeca; Brown, Alexandra; Nannicelli, Anna P.; Khare, Rahul; Holl, Jane L.
Abstract : Background—: Although best practices have been developed for achieving door-to-needle (DTN) times ⩽60 minutes for stroke thrombolysis, critical DTN process failures persist. We sought to compare these failures in the Emergency Department at an academic medical center and a community hospital. Methods and Results—: Failure modes effects and criticality analysis was used to identify system and process failures. Multidisciplinary teams involved in DTN care participated in moderated sessions at each site. As a result, DTN process maps were created and potential failures and their causes, frequency, severity, and existing safeguards were identified. For each failure, a risk priority number and criticality score were calculated; failures were then ranked, with the highest scores representing the most critical failures and targets for intervention. We detected a total of 70 failures in 50 process steps and 76 failures in 42 process steps at the community hospital and academic medical center, respectively. At the community hospital, critical failures included (1) delay in registration because of Emergency Department overcrowding, (2) incorrect triage diagnosis among walk-in patients, and (3) delay in obtaining consent for thrombolytic treatment. At the academic medical center, critical failures included (1) incorrect triage diagnosis among walk-in patients, (2) delay in stroke team activation, and (3) delay in obtaining computed tomographic imaging. Conclusions—: Although the identification of common critical failures suggests opportunities for a generalizable process redesign, differences in the criticality and nature of failures must be addressed at the individual hospital level, to develop robust and sustainable solutions to reduce DTN time. Abstract : Supplemental Digital Content is available in the text.